2013
DOI: 10.1111/ene.12228
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of first‐ever ischaemic stroke in European young adults: the 15 cities young stroke study

Abstract: The etiology of IS in young adults has clear gender-specific patterns that change with age. A notable portion of these patients remains without an evident stroke mechanism according to TOAST criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
98
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 37 publications
15
98
1
2
Order By: Relevance
“…This is in line with recent studies on young and middle‐aged patients 5, 17, while others have observed a further increase in small‐vessel occlusion at older ages 22. Large‐artery atherosclerosis followed a similar time course as small‐vessel occlusions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with recent studies on young and middle‐aged patients 5, 17, while others have observed a further increase in small‐vessel occlusion at older ages 22. Large‐artery atherosclerosis followed a similar time course as small‐vessel occlusions.…”
Section: Discussionsupporting
confidence: 91%
“…This constellation may be explained by high rates of cardiac disorders with low or uncertain risk, such as patent foramen ovale, among young patients 5, 19, 20, whereas high‐risk disorders, such as atrial fibrillation, increased dramatically with age 19, 20. The present data support this, as we identified AF as an important risk factor from the 4th decade, thereafter consistently increasing throughout the 10th decade.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Despite extensive etiologic workup, one third of IS in the young remains without identified pathogenesis (ie, cryptogenic IS). 1,3,4 Data on clinical outcomes in young patients with cryptogenic IS are limited.…”
mentioning
confidence: 99%